Identification And Inventory of The Types Of Bacteria Found At The Base Of The Sebangau River Pier Palangka Raya City - Suraya, Ummi; Yasin, M. Noor (Program Studi Budidaya Perairan Universitas Mataram, 2024)
This research was conducted with the aim of. to identify and invetarize the types of bacteria found in the Sebangau River Pier Base in Palangka Raya City. The implementation time was in November 2021 with a descriptive research method with sampling at the Sungai Sebangau Pier Base in Palangka Raya City and sample testing was carried out at the Palangka Raya Quarantine and Quality Control Station Laboratory. The results of this study found 7 positive and 12 gram-negative isolates with 12 different types of bacteria and bacterial characteristics, namely, Aeromonas hydrophila, Aeromonas sobria, Aeromonas caviae, Citrobacter freundii, Edwardseilla tarda, Escherichia coli, Staphylococcus aureus, Staphylococcus epidermidis, Plesiomonas shigelloides, Bacillus subtilis, Listeria sp, and Enterobacter cloacae.